Using student voice to escape the spider s web: A methodological approach to de-victimizing students with ADHD. - MC GUCKIN, CONOR; CARR-FANNING, KATE; SHEVLIN, MICHAEL GERALD (My University, 2013)
After innumerable hours and weeks spent adrift on the ocean of Attention Deficit Hyperactivity Disorder (ADHD) literature, searching for answers among the biological and behavioural social sciences, an infuriating amount of questions with no answers remained. Far from scientific experts and their de-contextualized truth claims, the voice of one young man, plucked us from their spider?s web. When posed the question ?what?s life with ADHD like?? he responded in kind, asking, ?how does an elephant tell a mouse what it?s like to be an elephant?? Apparently an ?insider? experiences barriers, just like an ?outsider?, each seeking a way out and in. One can recognize the privileged nature of experiential knowledge (Beresford, 2003), and still appreciate that developmentally generative social interactions depend upon shared systems of meaning (Gergen, 1994). Realising ?scientisms? (Thomas, 2009) inability to explicate either began the construction of the student voice methodology delineated in this paper. Student voice (i.e., voice) poses significant challenges and transformative potentials (Bragg, 2007); it is further problematized, and necessary, when it involves students with ADHD. Voice is inherently about power and knowledge (Thomas, 2011). As such, the social meaning of ADHD (Singh, 2012) must be considered to avoid re-victimizing the voices of students with ADHD (i.e., ADHD voice) or reproducing conventional knowledge (Fielding, 2004). This paper provides a pertinent analysis of voice methodology, and the limitations in prior ADHD voice research. The theoretical framework for the current study will also be explained, that is, the construction of a ?counter-discourse? to engage in meaningful dialogue (Taylor & Robinson, 2009).
PUBLISHED
Keywords: Education